High-density peptide arrays help to identify linear immunogenic B-cell epitopes in individuals naturally exposed to malaria infection - Jänisch, Thomas; Heiß, Kirsten; Bischoff, F. Ralf; Moldenhauer, Gerhard; Seeberger, Peter H.; Breitling, Frank (Molecular & cellular proteomics, 2019)
Graphical Abstract - Download figureOpen in new tabDownload powerpoint - - Highlights - Profiling antibody responses of patients with naturally acquired malaria immunity.High-density peptide arrays featuring linear epitopes.Epitope mapping of known and potential novel vaccine candidates.Novel immunogenic epitopes discovered, and known antibody target motifs confirmed. - High-density peptide arrays are an excellent means to profile anti-plasmodial antibody responses. Different protein intrinsic epitopes can be distinguished, and additional insights are gained, when compared with assays involving the full-length protein. Distinct reactivities to specific epitopes within one protein may explain differences in published results, regarding immunity or susceptibility to malaria. We pursued three approaches to find specific epitopes within important plasmodial proteins, (1) twelve leading vaccine candidates were mapped as overlapping 15-mer peptides, (2) a bioinformatical approach served to predict immunogenic malaria epitopes which were subsequently validated in the assay, and (3) randomly selected peptides from the malaria proteome were screened as a control. Several peptide array replicas were prepared, employing particle-based laser printing, and were used to screen 27 serum samples from a malaria-endemic area in Burkina Faso, West Africa. The immunological status of the individuals was classified as “protected” or “unprotected” based on clinical symptoms, parasite density, and age. The vaccine candidate screening approach resulted in significant hits in all twelve proteins and allowed us (1) to verify many known immunogenic structures, (2) to map B-cell epitopes across the entire sequence of each antigen and (3) to uncover novel immunogenic epitopes. Predicting immunogenic regions in the proteome of the human malaria parasite Plasmodium falciparum, via the bioinformatics approach and subsequent array screening, confirmed known immunogenic sequences, such as in the leading malaria vaccine candidate CSP and discovered immunogenic epitopes derived from hypothetical or unknown proteins.
Gesehen am 26.03.2020